The Novel as Third Space in the Struggle for One’s Own Place: Witold Gombrowicz’s Hidden Polemic with German Literature in Pornografia - Gall, Alfred (Tematy i Konteksty, 2021)
This paper deals with Gombrowicz’s novel Pornografia which can be interpreted as a third space where different literary discourses and philosophical concepts are interwoven. In this respect two German authors deserve special attention: Thomas Mann and Friedrich Nietzsche. It is the aim of this article to show to what extent Gombrowicz refers to the writings of these two authors in his attempt to establish himself as an important writer during his exile in Argentina. The novel Pornografia works in this respect as a sphere of interferences and a space of emerging hybridity, where Gombrowicz creates a special textuality consisting of hidden references to and even polemic with both Mann and Nietzsche. The notion of conflict is thus applicable in the description of Gombrowicz’s literary practice in this novel.